Pengembangan Buku Saku Sebagai Bahan Ajar Kearsipan Kelas X OTKP SMK Negeri 1 Jombang - Setiyaningrum Setiyaningrum; Bambang Suratman (Universitas Negeri Surabaya, 2020)
This study aims to 1) the results of the development of pocket books as class X archival teaching materials OTKP SMK Negeri 1 Jombang through a scientific approach according to K13 revised 2017, 2) the feasibility of developing pocket books as teaching materials archival class X OTKP SMK Negeri 1 Jombang through a scientific approach according to K13 revised 2017, and 3) the responses of students in class X OTKP SMK Negeri 1 Jombang through a scientific approach according to K13 revised 2017. The development model used in this study is the 4D model from Thiagarajan (Define-Design-Develop-Dessiminate). Disseminate stage was not carried out because this research only reached the development stage. This research was conducted on 20 students of class X OTKP 1 at SMK Negeri 1 Jombang. Instruments used in this study included validation sheets of material, language, graphics, and student response sheets using data analysis techniques on the results of the percentage of the feasibility of a pocket book. With the results of the validation of material experts by 90%, language experts by 80%, and graphic experts by 94%. The total validity of the whole validation was 89.75% with very proper interpretation. Based on students' responses got 96.4% results with very good interpretation. It can be concluded that the research into the development of pocket books as archival teaching materials with very strong interpretation criteria is stated to be well used as supporting teaching materials.